Comparative Psychoanalytic Study Of Poe’s “the Oval Portrait” And Hawthorne’s “the Birthmark” - Hejazi Bayan (The Journal of Studies in Language, Culture and Society, 2025)
The present study discusses Psychological concepts such as id, Eros, obsession, narcissism, and aggression as they are represented in Hawthorne’s “The Birthmark” (1843) and Poe’s “The Oval Portrait” (1842). These Dark Romantic works focus on depicting the evilness of human beings as a reaction against Puritan beliefs. The study's main aim is to introduce the similar mentality of male characters in both stories and how their unconscious mind plays a huge role in shaping their reactions. Moreover, it emphasizes how they are controlled by their impulses which lead them to sacrifice their wives for achieving stability. Several Psychological concepts are discussed such as the pleasure principle and obsessive jealousy that reinforce male characters’s evilness and aggression. Thereafter, a discussion is raised to answer questions on how obsession and narcissism limit the protagonists’ understanding of the horrific situation and indulge them in a defence mechanism against threats. Their lack of awareness and acting on their impulses lead them to realize their fallibility and imperfection.